Craniomandibular osteopathy in a West Highland White Terrier - Macedo, Aline Schafrum [UNESP]; Casagrande, André Jayr; Friesen, Rodrigo; Minto, Bruno Watanabe [UNESP] (My University, 2015)
Background: Craniomandibular osteopathy is a bone disorder that occurs in dogs but is not very commonly reported. It is characterized by a non-neoplastic bilaterally symmetrical irregular proliferation of skull or long bones. Immature dogs are most commonly reported with age ranging from three to eight months. The aim of this paper is to report a case of CMO in a West Highland White Terrier. Case: A 5-month-old entire West Highland white terrier was referred to the Veterinary Hospital with sudden history of severe pain and mandibular swelling, dysphagia, lethargy and weight loss. On physical examination the dog was quiet, alert and responsive. There was thickening of the mandibular bodies with pain at palpation and when opening the mouth. Complete blood count was within normal range. Simple radiographs demonstrated discrete and active new bone formation on the ventral aspect of the mandibular body. Carprofen, dypirone and tramadol were prescribed twice daily for 10 days. 30 days later new radiographs showed more extensive areas of periosteal proliferation advancing to the temporomandibular joint and progression of the looseness of the characteristic compact appearance of lamellar bone of the mandible. The dog was more lethargic, not eating well and in pain. Medication was again prescribed but the treatment was unsuccessful. The dog returned for consultation with severe pain, dysphagia and dramatic weight loss. The dog's owner opted then for euthanasia. Necropsy was performed and histopathological exam revealed irregular and plentiful radiating bony trabeculae composed mostly of woven bone, and the trabecular surfaces displayed scalloping and large number of osteoclasts and osteoblasts, confirming the diagnosis. Discussion: Craniomandibular osteopathy has been reported in West Highland and Scottish Terriers, and also in Boston Terrier, Cairn Terrier, Shetland Sheepdog, Labrador Retriever, Danish, English Bulldog, Doberman Pinscher, Irish Setter and Boxer. It is also known as 'lion jaw' or 'Westie disease' because the most commonly affected breed is the West Highland White Terrier. An autosomal recessive mode of inheritance has been suggested for terriers breeds. Other theories for the occurrence of CMO in other breeds have been suggested and involve other factors such as bacterial (Escherichia coli) or viral (canine distemper virus) infections. The main clinical signs are basically enlarged and painful jaw, drooling, and intermittent fever sometimes as well as lethargy, as observed in this case. Primarily the bones of the skull are affected although there are reports of this condition on the metaphyses of long bones even leading to angular deformities. The dog on this case didn't have any long bones alterations. In severe cases the disease may progress to ankylosis of the temporomandibular joint, which seemed to be occurring as the disease progressed to this joint. Diagnosis is based on clinical, radiographic and histopathological examination and was correctly made and confirmed by necropsy. The prognosis for the disease is usually good, normally clinical signs resolve when the animal reaches about 1 year of age, unless there is involvement of the temporomandibular joint because it will likely lead to ankylosis. Early diagnosis is very important for pain control and supportive and symptomatic medical management of craniomandibular osteopathy, a condition that has no cure so far. Anti-inflammatory drugs are the treatment of choice and were used in this case. Unfortunately this patient didn't respond well to medical management and progressed to a condition incompatible with life due to dysphagia and severe pain, so euthanasia was performed.
Keywords: Animal; Canine; Mandible; Osteoproliferative disorder; Skull